Neutrophil extracellular traps (NETs) in patients with STEMI. Association with percutaneous coronary intervention and antithrombotic treatments. Issue 213 (May 2022) - Ferré-Vallverdú, Maria; Latorre, Ana María; Fuset, María Paz; Sánchez, Elena; Madrid, Isabel; Ten, Francisco; Vallés, Juana; Santos, María Teresa; Bonanad, Santiago; Moscardó, Antonio
Abstract: Background: Neutrophil extracellular traps (NETs) are formed by DNA, histones and proteolytic enzymes, and are produced by activated neutrophils through different mechanisms. In turn, NETs can activate platelets and coagulation cascade favoring thrombotic processes. The aims of this study were to analyze levels and kinetics of NETs in ST-segment elevation myocardial infarction (STEMI) patients and correlate them with antithrombotic therapy and cardiovascular outcomes at follow-up. Methods: 150 consecutive STEMI patients referred to primary percutaneous coronary intervention (pPCI) were included. Citrate anticoagulated blood was extracted immediately before pPCI, 30 min and 24 h after the procedure. As markers of NETS cell free DNA (cfDNA), nucleosomes and citrullinated Histone 3 (citH3) were determined. 46 healthy subjects were included as controls. Patients were follow-up for 1.4 ± 0.56 years. Results: Before pPCI, NETs markers were elevated in STEMI patients compared to healthy controls ( p  < 0.05); these increased significantly 30 min post pPCI ( p  ≤ 0.001) and decreased at 24 h but remained elevated compared with the control group ( p  < 0.05). Patients treated with bivalirudin presented a lower increase of NETs 30 min post pPCI compared to patients treated with heparin ( p  < 0.05). Cardiovascular risk factors or type of stent implanted did not modify NETs levels. Cit3H (HR = 3.74; 95%CI 1.05–13.4; p  = 0.042) and left ventricular ejection fraction ≤35% (HR = 6.84; 95%CI 2–23; p  = 0.002) were independent predictors of composite endpoint of myocardial infarction, stroke, stent thrombosis and/or cardiovascular-cause death. Conclusions: NETs were elevated in STEMI patients, increased by pPCI and decreased thereafter. One of the most specific NETs markers was associated with cardiovascular outcomes.